EFFECT OF MINDFULNESS INTERVENTION ON THE INTENSITY OF PAIN IN NASOPHARYNGEAL CANCER PATIENTS UNDERGOING RADIATION TREATMENT - Anna Jumatul Laely; Awal Prasetyo; Chandra Bagus Ropyanto (Belitung Raya Foundation, Indonesia, 2018)
Background: Physical responses that occur in patients with nasopharyngeal cancer are the emergence of pain due to the effects of treatment. The problem of pain in these patients at the stage of treatment remains critical to solve because it can cause comorbidity, psychological trauma and mortality. Mindfulness intervention is considered useful in transforming consciousness into the stage of acceptance. Objective: This study aims to determine the effect of mindfulness intervention on the intensity of pain in nasopharyngeal cancer patients undergoing radiation treatment. Methods: This was a quasi-experimental study with pretest posttest control group design. Thirty patients were selected using consecutive sampling, which divided into experiment and control group. Visual Analogue Scale (VAS) was used to measure pain. Each respondent received mindfulness intervention for six sessions, divided into three meetings. Paired t-test was used for data analysis. Results: The results showed a significant reduction of pain from 4.12 (moderate pain) to 3.06 (mild pain) in the experiment group. There was a significant difference in pain level before and after mindfulness intervention (p= 0.001). Conclusion: Mindfulness is effective in reducing pain intensity level in nasopharyngeal cancer patients undergoing radiation therapy.